WSPÓLNOTOWOŚĆ HYBRYDOWA JAKO KATEGRORIA W OGLĄDZIE GRUP STUDENCKICH - Bochno, Ewa (Rocznik Pedagogiczny, 2018)
The paper scrutinises the university as a place for functioning within the community of student groups with relations and activities which are conducive or detrimental to the creation of the com- munity. An attempt was made to achieve two goals. First of all, to indicate the potential of a theo- retical and practical category of a hybrid, as well as a newly introduced, related category of hybrid community. Secondly, in relation to own research findings on dean’s student groups, the potential of their application when perceiving the groups through the category of hybrid community.